2017
DOI: 10.21089/njhs.24.0163
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors and Complications in Measles Mortalities

Abstract: Abstract:To determine the risk factors and complications in patients expired due to measles. Background:Measles is one of the vaccine-preventable diseases. Mortality and morbidity due to it has been decreased in many countries with preventive measures. However, epidemics occur off and on in some communities. Pakistan has faced an epidemic in 2012-13. Started from one province and affected others. Due to some risk factors, Pakistani children suffered from many complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…On the other hand, Akramuzzaman et al showed Diarrhoea as a complication in most cases. Rana et al showed history of contact with measles patients in 28% cases which is nearer to other study 16 . In our study, two cases of fully vaccinated patients developed measles.…”
Section: Resultsmentioning
confidence: 46%
See 1 more Smart Citation
“…On the other hand, Akramuzzaman et al showed Diarrhoea as a complication in most cases. Rana et al showed history of contact with measles patients in 28% cases which is nearer to other study 16 . In our study, two cases of fully vaccinated patients developed measles.…”
Section: Resultsmentioning
confidence: 46%
“…15 The Measles cases of our study came to hospital with complications, mostly it was respiratory tract Infection like pneumonia (60%) followed by diarrhoea associated with pneumonia in 35.56% cases. Rana MN showed Pneumonia with super-added bacterial infections were present in 100% cases 16 . On the other hand, Akramuzzaman et al showed Diarrhoea as a complication in most cases.…”
Section: Resultsmentioning
confidence: 96%